The impact of unilateral and bilateral plyometric training combined with linear sprints on physical performance in youth male elite futsal players - Neves, T. A., Soalheiro, I.; Winckler, C.; Michalsik, L. B.; Ramirez-Campillo, R.; Guerra, R. L. F. (International Journal of Sports Physiology and Performance, 2025)
Purpose: To compare the effect of linear sprint training combined with plyometric training involving unilateral compared with bilateral exercises on youth male elite futsal players` physical performance.